Financial Feasibility Analysis and Development Strategies of Small-Scale Peranakan Etawa (PE) Dairy Goat Enterprises in Kediri Regency - Yunia Chrismonica; Imam Mustofa; Wiwik Misaco Yuniarti; Emy Koestanti Sabdoningrum; Nusdianto Triakoso; Lita Rakhma Yustiana (Universitas Airlangga, 2026)
The Etawa crossbred (PE) dairy goat enterprise has significant potential to increase the supply of animal protein while improving farmers’ income, particularly in Kediri Regency, which offers favorable conditions for dairy goat farming development. This study aimed to analyze the financial feasibility, identify internal and external influencing factors, and formulate development strategies for PE dairy goat enterprises in Kediri Regency. The research was conducted in January 2026 using a descriptive quantitative approach. Respondents were selected purposively based on the criteria of small-scale farms owning 1–35 goats and having at least five years of farming experience. Of the 30 identified farms, 14 were selected as respondents. Data were collected through interviews, questionnaires, field observations, and supporting secondary sources. Financial feasibility was analyzed using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Benefit–Cost Ratio (B/C ratio), Return on Investment (ROI), and Break-Even Point (BEP). Strategic analysis was conducted using SWOT analysis supported by the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Internal–External (IE) matrices. The results showed that most enterprises were financially feasible. Nearly all farms met the NPV and IRR criteria, except farm number 12, while all enterprises fulfilled the PP, B/C ratio, and ROI standards. SWOT analysis positioned the enterprises in Quadrant I, indicating aggressive development strategies focused on improving product quality, business management, and production risk control.